2019
DOI: 10.1017/s1092852919000804
|View full text |Cite
|
Sign up to set email alerts
|

Early seizures after ischemic stroke: focus on thrombolysis

Abstract: Introduction.Stroke is a significant underlying cause of epilepsy. Seizures due to ischemic stroke (IS) are generally categorized into early seizures (ESs) and late seizures (LSs). Seizures in thrombolysis situations may raise the possibility of other etiology than IS.Aim.We overtook a systematic review focusing on the pathogenesis, prevalence, risk factors, detection, management, and clinical outcome of ESs in IS and in stroke/thrombolysis situations. We also collected articles focusing on the association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 110 publications
(364 reference statements)
1
33
0
Order By: Relevance
“…In our study, 4/90 patients (4.4%) developed acute symptomatic seizures. This is similar to previously reported rates for patients treated with intravenous thrombolytics without thrombectomy [7,8], but reports range from 1% to 15 % [6,9]. So far, described risks of acute symptomatic seizures or PSE after thrombectomy are relatively lowgiven that patients selected for therapy are often at risk of very large lesions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 4/90 patients (4.4%) developed acute symptomatic seizures. This is similar to previously reported rates for patients treated with intravenous thrombolytics without thrombectomy [7,8], but reports range from 1% to 15 % [6,9]. So far, described risks of acute symptomatic seizures or PSE after thrombectomy are relatively lowgiven that patients selected for therapy are often at risk of very large lesions.…”
Section: Discussionsupporting
confidence: 89%
“…Reported rates of acute symptomatic seizures (seizures within one week of stroke) in thrombolysis-treated patients vary from approximately 1% to 15% [6][7][8][9]. In three relatively recent studies of thrombolysis-treated cohorts, PSE (seizures occurring >1 week after stroke) was reported in 5.8%-16.7% [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, specific stroke types, such as hemorrhagic stroke and total anterior circulation stroke are strongly correlated with increased chance of PSE (Leone et al, 2009; Graham et al, 2013). ES, with an overall prevalence of 3.8% (Feher et al, 2019), is also correlated with similar stroke groups, being more common after hemorrhagic (8.4%) compared to ischemic stroke (2.4%) (Szaflarski et al, 2008). The extent of cortical injury is also considered to be an important issue for both ES and LS, as studies have shown that the involvement of the parietotemporal cortex, supramarginal gyrus and superior temporal gyrus seems to be connected to post stroke epileptogenesis (Zhao et al, 2018).…”
Section: Post Stroke Seizures and Epilepsymentioning
confidence: 95%
“…The presumed pathophysiology explaining the emergence of early seizures by ischemic strokes is linked to the transient cellular biochemical dysfunctions in the brain tissue that occur following acute ischemia (Feher et al., 2020 ) A lower threshold for depolarization from local excitotoxicity secondary to increased glutamate along with an increased intracellular calcium and sodium inflow results in lowering the seizure threshold for depolarization and leading to electrically irritable tissue with consequent hyperexcitability and possible neuronal injury (Camilo & Goldstein, 2004 ).…”
Section: Introductionmentioning
confidence: 99%